Preparation and characterization of biocomposites from oil palm mesocarp fiber and poly (butylene succinate) - Then, Yoon Yee (2015)
In the present work, biocomposites were prepared from poly(butylene succinate) (PBS) and various weight percentages (10-70 wt%) of oil palm mesocarp fiber (OPMF) by using a melt blending technique followed by hot-press moulding. Surface modification of OPMF was carried out via four approaches, namely alkali, superheated steam, combination superheated steam-alkali, and bleaching treatments, aiming at improving the interfacial adhesion between the hydrophilic OPMF and the hydrophobic PBS. Additionally, silane coupling agent of 3-aminopropyltrimethoxysilane (APS) was also introduced into the biocomposite system to induce some chemical linkage between OPMF and PBS. Apart from that, electron beam irradiation (EBI) was also applied to improve the tensile properties of OPMF/PBS biocomposites. The results indicated that the tensile, flexural, and impact properties of OPMF/PBS biocomposites were comparable and even better than those of OPMF/polypropylene (OPMF/PP) and oil palm empty fruit bunch fiber/PBS (OPEFBF/PBS) biocomposites. Additionally, the biodegradation rate of OPMF/PBS biocomposites was also noticeably higher than those of OPMF/PP biocomposites, and showed comparable values to those of OPEFBF/PBS biocomposites. The chemical compositions of OPMF were changed after various treatment processes as validated by chemical analysis and Fourier transform infrared (FTIR) spectroscopy. The treated OPMF under microscopy observation showed relatively rough texture surfaces due to the elimination of impurities and hemicellulose. The crystallinity index and thermal stability of treated OPMF were relatively higher than that of untreated OPMF as determined by using X-ray diffraction (XRD) analysis and thermogravimetric analysis (TGA), respectively. A reduction in water uptake of fiber after treatments was also noted. The OPMF treated at 5 wt% NaOH solution for 180 min, and superheated steam temperature of 220 °C for 60 min gave biocomposites with best combinations of tensile strength, tensile modulus, and elongation at break. The subsequent alkali treatment of superheated steam-treated OPMF with 2 wt% NaOH for 180 min enhanced further the tensile properties of the corresponding biocomposite. The interfacial adhesion between treated OPMF and PBS was improved considerably as indicated by scanning electron micrographs. The treated OPMF/PBS biocomposites also exhibited higher thermal and dimensional stabilities, as well as more resistance to microorganism attacks in comparison to that of untreated OPMF/PBS biocomposite. The addition of 2 wt% APS into the PBS biocomposite filled with combination superheated steam-alkali treated OPMF further enhanced the tensile, flexural, and impact strengths by 16, 26, and 8%, respectively, relatively to biocomposite without APS addition. Similarly, the resistance to water uptake and thickness swelling of this biocomposite was improved by 34 and 49%, respectively. The SEM observation of the tensile fractured surface showed that APS further improved the interfacial adhesion between combination superheated steam-alkali-treated OPMF and PBS. Some chemical linkages have been formed between the treated OPMF, PBS, and APS, mainly via hydrogen bonding as indicated by FTIR spectroscopy. The biocomposites fabricated from PBS and bleached OPMF showed improvement of 54, 830, and 43% in tensile strength, tensile modulus, and elongation at break as compared to that of untreated OPMF. In addition, bleached OPMF/PBS biocomposites also showed better flexural and impact performance in comparison to that of untreated OPMF/PBS biocomposite. For EBI treatment, the results indicated that OPMF/PBS biocomposites irradiated with 20 kGy of applied dosage showed a considerable improvement of 47% in tensile strength, 772% in tensile modulus and 28% in elongation at break relative to nonirradiated OPMF/PBS biocomposite. The water uptake and thickness swelling of OPMF/PBS biocomposites were also reduced after EBI treatment. The OPMF/PBS biocomposites fabricated from this work showed potential application in particleboards, and dashboard for car interior compartment.